2019
DOI: 10.25134/unifikasi.v6i2.1849
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Sharia Mutual Fund as an Investment Means to Promote Financial Inclusion in Indonesia

Abstract: Sharia mutual fund can be used as an investment alternative for investors, especially for small investors or retailers. The excess of sharia mutual funds that can be reached by all groups shall be a means to promote financial inclusion in Indonesia. Based on data released by the Bank of Indonesia (BI), in 2018, financial inclusion or access to financial institutions of the Indonesian citizens is only 49% (forty-nine percent). Therefore, we need a concrete strategy to promote financial inclusion in Indonesia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results show that ease of access can increase investment opportunities in India. Asmara and Abubakar (2019) also found that ease of access could encourage an increase in investments in mutual funds. Based on this, the following hypothesis is proposed: H5: Financial inclusion has a positive effect on mutual fund investment decisions.…”
Section: Financial Inclusion and Investment Decision Mutual Fundsmentioning
confidence: 97%
See 3 more Smart Citations
“…The results show that ease of access can increase investment opportunities in India. Asmara and Abubakar (2019) also found that ease of access could encourage an increase in investments in mutual funds. Based on this, the following hypothesis is proposed: H5: Financial inclusion has a positive effect on mutual fund investment decisions.…”
Section: Financial Inclusion and Investment Decision Mutual Fundsmentioning
confidence: 97%
“…Paramasivan and Ganeshkumar (2013) and Sekhar (2013) show that financial inclusion can improve investment decisions. Asmara & Abubakar (2019) show that financial inclusion has the potential to increase investment decisions. Based on this, the following hypothesis is proposed: H6: Financial inclusion can mediate the influence of financial literacy on mutual fund investment decisions.…”
Section: Financial Literacy Financial Inclusion and Investment Decisi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of sharia financing must fulfill two very important aspects, namely the syar'i aspect in the realization of financing that must be oriented towards Islamic sharia, and the economic aspect by considering the benefits for the institution and its customers Ilyas (2019). Sharia mutual funds can be one of the means in promoting financial inclusion program as it can be reached by all groups, especially small investors or retailers Asmara and Abubakar (2019). Furthermore, it is stated that the development of the financing concept of the CSQI model is expected to be able to minimize the occurrence of price speculation, reduce the trend of increasing beef cattle commodity prices from year to year (price stabilization) and provide investment certainty for smallholder livestock businesses and at the same time ensuring the quality and quantity of cattle for Qurban participants Novra and Suparjo (2020).…”
Section: Brief Description Of the Cqsi Programmentioning
confidence: 99%